Mechanical properties of concrete produced with alkali-activated slag-fly ash and recycled concrete aggregate and designed using the densified mixture design algorithm (DMDA) method: Effects of recycled aggregate content and alkaline solution - Vo, Duy-Hai; Tran Thi, Khanh-Dung; Hwang, Chao-Lung; Liao, Min-Chih; Hsu, Wei-Liang; Yehualaw, Mitiku Damtie (Developments in the built environment, 2023)
The purpose of this study was to evaluate the mechanical properties of concrete specimens produced with recycled aggregate (RA) from construction demolition waste (CDW) based on alkaline activated slag-fly ash (AASF). The recycled aggregate concrete mixtures (RAC) were designed using DMDA method, with RA used as a 30%, 40%, and 50% partial replacement for natural aggregate (Category 1) and with Na2O doses of 4%–8% and modulus ratios of 0.6–1.4 (Ms = SiO2/Na2O; Category 2). The results showed that the inclusion of RA negatively affected the mechanical properties of RAC specimens, with recycled coarse aggregate exhibiting less of a negative effect than recycled fine aggregate. The concrete mixtures exhibited mechanical strength values of 20.7–35.9 MPa and UPV values of 3692–4200 m/s at 28 days of curing age. Concrete characteristics were significantly better in the mixtures produced using higher alkaline concentrations than in those produced using lower alkaline concentrations. •Eco-friendly concrete specimens are produced using several RA-replacement levels and alkaline parameters.•The DMDA method is used to determine the optimum level of FA densified mixture and hydration reaction.•High RA content significantly and negatively affects the properties of RAC specimens.•Using a higher alkaline solution minimizes the negative influence of RA on concrete properties.